IMPLEMENTASI SISTEM SEWA MENYEWA LINEN HOTEL DALAM PERSPEKTIF FIQIH MUAMALAH (STUDI PADA BARACK PROFESIONAL LAUNDRY KEDIRI) - Hisam Asngari (LPPM INSTITUT AGAMA ISLAM HASANUDDIN PARE, 2025)
One of the muamalah activities is doing business. Business is defined as an activity carried out by humans to obtain income or income or fortune in order to meet the needs and desires of their lives by managing economic resources effectively and efficiently. Substantively in accordance with the development of practical science, business activities consist of activities in the fields of production, marketing, finance and human resources. This research focuses on the linen leasing system applied by the laundry, which is usually a leasing system correlated with the main business of the laundry, namely washing activities carried out by the laundry by paying attention to several pillars and conditions of ijaroh. the objectives of this study include: 1) To find out the lease of linen at Barack Professional Laundry; 2) To find out the lease of linen at Barack Professional Laundry from the perspective of Fiqh Muamalah.The research method uses a qualitative approach with a case study research type. Data were obtained from primary and secondary data. Data analysis was carried out in three ways, namely: reduction, exposure, conclusion drawing. Linen leasing at Barack Professional Laundry is done by leasing linen owned by the laundry to the hotel, but not all hotels use this leasing service. Only hotels that have not met the par stock of linen use linen rental services. Linen leasing has fulfilled the pillars and conditions of ijaroh.